Hot Licks and Rhetoric: Collecting, Community, and Disruptive Literacies - (:unkn) unknown (My University, 2022)
This ethnographic dissertation investigates the activities and tactical technical communications (TTC) of underground music collectors. Through this it explores the concepts of community and institution that compositionists and technical writing scholars use as ways to address social influences on writing, but which fail to explain how these milieus influence the writers and their genres. Collectors of Recordings of Independent Origin (ROIOs), through the use of increasingly disruptive technologies, moved from passive listeners to active producers of music for sharing freely, garnering opposition from the music industry as their activities moved online. This study views the relationship between the music industry, ROIO collectors, and bootleggers through an activity theory lens and applies rhetorical genre analysis to collectors’ voluntary, colloquially written, but highly technical documentation. These methods, coupled with surveys of ROIO collectors, creators, and site administrators, reveal high interactivity and cooperation between these seemingly oppositional groups. By focusing away from social contexts and toward the literacies employed within them and the purposes to which these literacies are applied, this study suggests that the way in which technologies disrupt societies and organizations is analogous to the way in which social contexts influence writing and genre. These findings allow for a more literacy-connected way of seeing institution and a purpose-driven view of community that return analytical focus to writers and the purposes for which write. In turn, these ideas allow us to view tactics, currently viewed in TTC scholarship as opposition to institutional preferences or strategies, in terms of both multiperspectivity of an activity system’s object and the available literacies employed for the writer’s purposes.
Keywords: Activity Theory; Community; Disruptive Technology; Genre; Literacy; Tactical Technical Communication